Bacteriochlorophyll f: properties of chlorosomes containing the "forbidden chlorophyll" - Vogl, Kajetan; Tank, Marcus; Orf, Gregory S.; Blankenship, Robert E.; Bryant, Donald A. (Frontiers in Microbiology, 2012)
The chlorosomes of green sulfur bacteria are mainly assembled from one of three types of bacteriochlorophylls, BChls c, d, and e. By analogy to the relationship between BChl c and BChl d (20-desmethyl-BChl c), a fourth type of BChl, BChl f (20-desmethyl-BChl e), should exist but has not yet been observed in nature. The bchU gene (bacteriochlorophyllide C-20 methyltransferase) of the brown-colored green sulfur bacterium Chlorobaculum limnaeum was inactivated by conjugative transfer from Eshcerichia coli and homologous recombination of a suicide plasmid carrying a portion of the bchU. The resulting bchU mutant was greenish brown in color and synthesized BChl fF. The chlorosomes of the bchU mutant had similar size and polypeptide composition as those of the wild type (WT), but the Qy absorption band of the BChl f aggregates was blue-shifted 16 nm (705 nm vs. 721 nm for the WT). Fluorescence spectroscopy showed that energy transfer to the baseplate was much less efficient in chlorosomes containing BChl f than in WT chlorosomes containing BChl e. When cells were grown at high irradiance with tungsten or fluorescent light, the WT and bchU mutant had identical growth rates. However, the WT grew about 50% faster than the bchU mutant at low irradiance (10 µmol photons m-2 s-1). Less efficient energy transfer from BChl f aggregates to BChl a in the baseplate, the much slower growth of the strain producing BChl f relative to the WT, and competition from other phototrophs, may explain why BChl f is not observed naturally.